Strategie, polityki i narzędzia wspierania kreatywności i innowacyjności w gospodarce w Unii Europejskiej. Praktyczne zastosowanie multilevel governance na poziomie krajowym i wspólnotowym - Bartoszewicz, Artur (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
The article analyzes the Lisbon Strategy and the Strategy Europe 2020 which concentrate on supporting economic innovation within the EU. Moreover EU common policies are discussed, particularly competition policy that sets the rules for public aid. The tools for supporting creativity and innovations are also discussed, beginning with the EU Framework Programs, operational programs on state level, and ending at common initiatives. Horizon 2020, a new framework program for the years 2014–2020, is particularly interesting in the context of creativity and innovations. Horizon 2020 includes actions aimed at increasing the level of innovation in economy and society of EU and its member states. The analysis was conducted in the context of mulitlevel governance in the areas of creativity and innovation in economy, culture and society.